THE PATTERN OF THORACIC INJURIES IN VICTIMS OF ROAD TRAFFIC ACCIDENTS: AN AUTOPSY BASED CROSS SECTIONAL STUDY (Journal of Forensic Medicine & Toxicology, 2022)
Introduction: Road Traffic Accident (RTA), in this era of urbanization, have emerged as a global health hazard because of the morbidity and mortality associated with them. In an RTA, often the thoracic injuries go unnoticed and are overlooked because of the resilient nature of the thoracic wall, which leads to the late detection of injuries and their fatal outcomes. Aim of the study: To evaluate the pattern of thoracic injuries in RTA and to find out the epidemiological parameters involved in RTA. Materials and Methods: In this autopsy based cross sectional study, 85 victims of fatal RTA were studied between 1st July 2019 to 31st December 2020 in the mortuary of AIIMS, Bhubaneswar. All the fatal RTA cases coming for autopsy were included in the study except decomposed and mutilated cases. Result: In this study, male two-wheeler drivers, belonging to the age group 21-40 years were most vulnerable to RTAs. Maximum number of RTAs were reported during Winter season. Inter-city roads witnessed majority of the RTAs and two-wheelers were the most common offending agent. Most of the RTAs occurred during late evening i.e.,
Keywords: Chest injuries; Road Traffic Accident; Injury pattern; Medicolegal autopsy; Blunt trauma